EFFECTS OF CALCIUM OIL IN COMMERCIAL RATIONS ON PHYSICAL COMPOSITION OF BROILER CARCASSES - P. A. D., Anggraeni; Candrawati, D. P. M. A.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - April, 2020)
The study aims to determine the effect of calcium oil administration in commercial rations on the composition of broiler chicken carcasses. This research was carried out for 35 days at the Farm Faculty of Animal Husbandry, Udayana University, Bukit Jimbaran. The design used completely randomized design (CRD) consisting of 4 treatments and 6 replications. Each plot was filled with 5 7 day-old broiler chickens with homogeneous body weight. The four treatments are chickens fed commercial rations without calcium oil as a control (A), by giving 1% of calcium oil in commercial rations (B), administering 2% of calcium oil in commercial rations (C), and administering 3% of calcium oil in commercial ration (D). The variables observed were carcass weight (g / tail), carcass meat percentage (%), carcass bone percentage (%), and percentage of subcutaneous fat (%). The results showed that carcass weight and bone percentage in chickens that received 1%, 2% and 3% calcium oil were not significantly different (P> 0.05) compared to chickens that did not get calcium oil (control). The percentage of chicken meat treated with calcium oil was significantly higher (P <0.05) compared to control, while the percentage of subcutaneous fat significantly decreased with the addition of calcium oil compared to control. From the results of the study it can be concluded that administration of calcium oil by 1-3% in commercial rations can increase the percentage of meat and reduce the content of subcutaneous fat in broiler chickens. Keywords: calcium oil, broiler meat, subcutaneous fat